Analysis Of The Contextual Approach (Contextual Teaching and Learning) in Improving Student Learning Outcomes - rikabima rika (CV Grasta Glory, 2026)
The Contextual Teaching and Learning (CTL) approach is a learning approach that discusses lesson material with students' real lives so that learning becomes more meaningful. This article aims to analyze the application of the Contextual Teaching and Learning (CTL) approach in improving student learning outcomes. The method used in writing this article is a literature study by examining several sources such as journals, books, and research that are relevant to the CTL approach in learning. The results of the study show that the application of the CTL approach can increase student activity in the learning process, help students understand concepts more deeply, and improve student learning outcomes. This is because in the CTL approach, students do not only receive material passively but are also directly involved in the process of discovering and linking knowledge with everyday experiences. Thus, the contextual teaching and learning approach can be an effective alternative to improve the quality of learning and student learning outcomes.